Factors Attributable to Cardiovascular Diseases in the Elderly Population of the Campo Alegre Resettlement, Tierralta, Córdoba - Carolina Castellanos Ramos; Brayan Domínguez Lozano; Daniela Jiménez Cordero; José Rocha Barraza (Revista Finlay)
Background: cardiovascular diseases are the leading cause of death worldwide, each year more people die from one of these diseases than from any other cause. Objective: to identify the risk factors for the development of cardiovascular diseases in the Campo Alegre resettlement, Tierra Alta, Córdoba during 2020-2021. Methods: a descriptive study was carried out in which adults over 60 years of age residing in the resettlement were included. The variables studied were: age and sex, marital status, socioeconomic status, educational level, work status, household or personal income, health history and healthy lifestyle conditions such as high blood pressure, type 2 diabetes mellitus, physical activity , healthy eating and daily food ration, weight control, drug dependence, medical control and hypercholesterolemia. They were given a survey focused on knowing the risks exposed to cardiovascular disease. The data was stored in Excel and analyzed in SPSS Statistics 26. Results: minimum ages (60 years) and maximum ages (76 years and over) were obtained. It was possible to show that arterial hypertension prevailed in the population for both sexes, the educational level is related to the educational level of the population, a greater number of cases was found in the population without studies. Conclusions: the frequency of risk factors for cardiovascular diseases present in the population warns about the need to develop health promotion and disease prevention plans in this area of the municipality of Tierralta, Córdoba, since it has been shown that this entails to consequences in the quality of life of the elderly population.